Invited review: Mechanisms of GTP hydrolysis and conformational transitions in the dynamin superfamily. Issue 8 (20th May 2016) - Daumke, Oliver; Praefcke, Gerrit J. K.
ABSTRACT: Dynamin superfamily proteins are multidomain mechano‐chemical GTPases which are implicated in nucleotide‐dependent membrane remodeling events. A prominent feature of these proteins is their assembly‐ stimulated mechanism of GTP hydrolysis. The molecular basis for this reaction has been initially clarified for the dynamin‐related guanylate binding protein 1 (GBP1) and involves the transient dimerization of the GTPase domains in a parallel head‐to‐head fashion. A catalytic arginine finger from the phosphate binding (P‐) loop is repositioned toward the nucleotide of the same molecule to stabilize the transition state of GTP hydrolysis. Dynamin uses a related dimerization‐dependent mechanism, but instead of the catalytic arginine, a monovalent cation is involved in catalysis. Still another variation of the GTP hydrolysis mechanism has been revealed for the dynamin‐like Irga6 which bears a glycine at the corresponding position in the P‐loop. Here, we highlight conserved and divergent features of GTP hydrolysis in dynamin superfamily proteins and show how nucleotide binding and hydrolysis are converted into mechano‐chemical movements. We also describe models how the energy of GTP hydrolysis can be harnessed for diverse membrane remodeling events, such as membrane fission or fusion. © 2016 Wiley Periodicals, Inc. Biopolymers 105: 580–593, 2016.